Pengaruh E-Commerce, Self Efficacy dan Penggunaan Sistem Informasi Akuntansi dalam Pengambilan Keputusan Berwirausaha pada Alumni Program Studi Akuntansi Universitas Nusa Cendana - Adelheid Moi Siba; I Komang Arthana; Herly M. Oematan (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
The purpose of this research is to determine the influence of e-commerce, self-efficacy, and accounting information systems in entrepreneurial decision making for alumni of the Nusa Cendana Kupang University Accounting Study Program partially and simultaneously. The data analysis technique used in this research is multiple linear regression analysis technique. The data collection technique was carried out by distributing questionnaires. The sample used in this research were alumni from the Undana Accounting study program. The results of this research show that partially e-commerce, self-efficacy, and accounting information systems influence the entrepreneurial decision making of alumni of the accounting study program. The variables e-commerce, self-efficacy, and accounting information systems simultaneously influence entrepreneurial decision making for Undana accounting study program alumni. It is hoped that this research will contribute to alumni in making entrepreneurial decisions. In this way, they can continue to develop their abilities and deepen their accounting knowledge to support success in entrepreneurship.